Charge and Spin Transport in an Organic Molecular Square. (20th August 2015) - Wu, Yilei; Nalluri, Siva Krishna Mohan; Young, Ryan M.; Krzyaniak, Matthew D.; Margulies, Eric A.; Stoddart, J. Fraser; Wasielewski, Michael R.
Abstract Understanding electronic communication among multiple chromophoric and redox units requires construction of well‐defined molecular architectures. Herein, we report the modular synthesis of a shape‐persistent chiral organic square composed of four naphthalene‐1, 8:4, 5‐bis(dicarboximide) (NDI) sides and four trans‐1, 2‐cyclohexanediamine corners. Single crystal X‐ray diffraction reveals some distortion of the cyclohexane chair conformation in the solid state. Analysis of the packing of the molecular squares reveals the formation of highly ordered, one‐dimensional tubular superstructures, held together by means of multiple [CH⋅⋅⋅OC] hydrogen‐bonding interactions. Steady‐state and time‐resolved electronic spectroscopies show strong excited‐state interactions in both the singlet and triplet manifolds. Electron paramagnetic resonance (EPR) and electron‐nuclear double resonance (ENDOR) spectroscopies on the monoreduced state reveal electron sharing between all four NDI subunits comprising the molecular square.